Pengaruh Tingkat Angkatan Kerja dan Pertumbuhan Ekonomi terhadap Tingkat Pengangguran di Indonesia - Iis Nawiyah; Agus Eko Sujianto; Tamara Nur Ayu Agnes; Indri Alya Sasabela; Alexza Alifia Nurinnisa (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This study looks into how Indonesia's unemployment rate is affected by both economic growth and the labor force. By analyzing economic and labor market data, this study aims to understand whether high economic growth is aligned with increased employment opportunities and a reduction in the number of unemployed. The ideal dimension of this study is linked to economic theories that connect economic growth with job creation, while its realistic dimension will reveal the extent to which these theories are reflected in the Indonesian context. Through interviews, observations, and data analysis, this study is anticipated to advance knowledge of the complex relationship between the labor force, economic growth, and the unemployment rate in Indonesia.